OPTICAL ABSORPTION STUDY OF NATURAL GARNETS OF ALMANDINE-SKIAGITE COMPOSITION SHOWING INTERVALENCE FE2+ + FE3+ → FE3+ + FE2+ CHARGE-TRANSFER TRANSITION - Taran M.N.; Matsyuk S.S.; Dyar M.D. (My University, 2007)
A broad (FWHM ≈ 7300 cm-1) intense band at ~21700 cm-l in the optical absorption spectra of natural Fe2+, Fe3+-rich garnets is attributed to electronic intervalence charge-transfer transitions (IVCT), VIIIFe2+ + VIFe3+ → VIIIFe3+ + VIFe2+. In Fe3+, Fe2+-bearing garnets of predominantly almandine compositions, this band causes yellowish tinges in addition to the pink color, typical of pure Fe3+-free almandines. In garnets from deeper-seated mafic granulites from kimberlite pipes in Siberia with high skiagite (Fe3 2+Fe2 3+Si3O12) contents, IVCT causes intense brownish-yellow colors. The relatively high energy of the band (~21700 cm-1) compared to diverse minerals showing IVCT between Fe2+ and Fe3+ in adjacent octahedral sites, is attributed to the charge-transfer transition taking place between Fe2+ and Fe3+ in non-equivalent, dodecahedral and octahedral sites of the garnet structure. Band intensity is directly correlated with the product of Fe2+ and Fe3+ as measured by Mössbauer spectroscopy. The energy of the IVCT band is nearly independent of temperature, whereas its intensity decreases slightly with increasing temperature. Pressure induces a weak shift of the band to lower energies, Δv/Ṗ= ≈ -75 cm-1/GPa, but intensity of the bands remains practically unchanged. Such temperature and pressure dependencies are quite different from those in other minerals showing IVCT between Fe2+ and Fe3+ in equivalent octahedral positions of structure.
Keywords: ELECTRONIC DD TRANSITIONS; GARNETS; INTERVALENCE CHARGE-TRANSFER TRANSITIONS; IRON IONS; MÖSSBAUER SPECTRA; OPTICAL ABSORPTION SPECTRA